Method for short-process preparation of high-purity vanadium for vanadium battery
Patent Information
- Application Number
- CN202611382434.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-09
AI Technical Summary
目前现有钒渣提钒工艺大多采用传统空气氧化焙烧体系,核心存在钒价态不可控、工艺繁琐、产品纯度低的问题,难以直接制备高纯四价钒电解液
1、本发明通过惰性气氛复合添加剂可控焙烧体系,可一步直接选择性制备四价钒,无需后续外加还原剂、无需高价钒还原工序,彻底规避传统工艺焙烧生成五价钒、必须额外还原制备四价钒的繁琐流程,大幅缩短钒电解液制备工序,降低还原剂耗材成本与工艺能耗,同时避免还原过程引入新杂质,从源头保障硫酸氧钒(VOSO4)电解液纯度与稳定性。
Smart Images

Figure CN122879526A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-purity vanadium preparation technology for vanadium batteries, and particularly relates to a short-process method for preparing high-purity vanadium for vanadium batteries. Background Technology
[0002] Vanadium redox flow batteries, with their unique advantages such as high safety, long cycle life, suitability for long-term energy storage scenarios, and no risk of thermal runaway, are one of the most promising technologies for industrialization in the long-term energy storage sector (4 hours or more). In recent years, the vanadium battery industry has experienced explosive growth, with vanadium resource consumption in the energy storage field increasing significantly year after year, and the process of large-scale commercialization accelerating. Market demand for high-purity vanadium raw materials specifically for vanadium batteries has surged. At the same time, the supply gap for high-quality battery-grade high-purity vanadium raw materials continues to widen. Traditional high-purity vanadium preparation processes are lengthy, energy-intensive, have limited purity, and insufficient production capacity, severely restricting the large-scale, low-cost deployment and promotion of the vanadium battery industry. Developing short-process, low-cost, and high-quality vanadium battery-specific high-purity vanadium preparation technology is of great industry urgency and practical need. Converter vanadium slag is a byproduct of vanadium-titanium magnetite steelmaking and is rich in vanadium. Currently, most existing vanadium slag extraction processes use traditional air oxidation roasting systems, which suffer from uncontrollable vanadium valence states, cumbersome processes, and low product purity, making it difficult to directly prepare high-purity tetravalent vanadium electrolytes.
[0003] Traditional vanadium extraction processes from vanadium slag often employ single sodium salt air oxidation roasting. During roasting, trivalent vanadium is deeply oxidized to pentavalent vanadium, making it impossible to directly obtain tetravalent vanadium. A secondary reduction with an additional reducing agent is necessary to prepare vanadium oxysulfate (VOSO4) electrolyte. This process is lengthy, consumes a large amount of reducing agent, and easily introduces impurities. During calcination roasting and acid leaching, vanadium and manganese are leached simultaneously, with a manganese content of 8-10 g / L. Manganese, iron, and other impurities are easily co-soluble in the leaching solution, leading to complex subsequent impurity removal processes, high production costs, and insufficient purity of the finished electrolyte. This severely restricts the efficient and low-cost preparation of high-purity vanadium electrolyte.
[0004] In response to the multiple technical shortcomings of existing high-purity vanadium preparation technologies, such as cumbersome processes, low leaching rates, the need for secondary reduction, co-dissolution of impurities, and high purification difficulty, there is an urgent need to develop a new resource-based process for the one-step directional preparation of tetravalent vanadium, high-selectivity and high-leaching-rate vanadium extraction, no additional reduction process, and a short and efficient process for the preparation of high-purity vanadium for vanadium batteries. Summary of the Invention
[0005] In view of this, the present invention discloses a short-process method for preparing high-purity vanadium for vanadium batteries.
[0006] The present invention adopts the following technical solution: A short-process method for preparing high-purity vanadium for vanadium batteries, the method comprising the following steps: S1. Raw material pretreatment: Magnetic vanadium spinel is obtained by magnetic separation of converter vanadium slag; the magnetic vanadium spinel is then subjected to grinding, weak magnetic separation and ultrasonic dispersion to obtain highly active vanadium spinel powder. S2. Preparation and extraction of tetravalent vanadium by calcination of composite additives: The highly active vanadium spinel powder described in S1 is mixed with the composite additives and then transferred to a heating furnace for calcination under an argon atmosphere. The calcined clinker is then leached in an aqueous solution at 25-95℃, and the leaching is separated by filtration to obtain vanadium-containing leachate and vanadium leaching tailings. The composite is Na2CO3-MnCO3-Fe2O3 or Na2CO3-MgCO3-Fe2O3. S3. Preparation of vanadium oxysulfate (VOSO4) electrolyte by extraction: Add acid to the vanadium-containing leachate described in S2 to adjust the pH value to acidic, and then sequentially pass it through a composite extraction system for mixed extraction, washing and purification with dilute sulfuric acid, and sulfuric acid back-extraction-graphite degreasing to obtain vanadium oxysulfate (VOSO4) electrolyte; the composite extraction system includes: a ternary compound system with P204 or P507 as the main extractant, TBP as the co-extraction agent, and sulfonated kerosene as the diluent; S4. Harmless treatment of tailings: The vanadium leaching tailings described in S2 are washed with warm water at 40-60℃ 2-4 times to obtain washing liquid, which is then used in the leaching process described in S2 for recycling. S5. One-step oxidation-hydrothermal direct precipitation of vanadium to prepare high-purity vanadium pentoxide (V2O5): Take the vanadium oxysulfate (VOSO4) electrolyte described in S3, add an oxidant to completely oxidize tetravalent vanadium to pentavalent vanadium, adjust the pH of the system to 1.2-3.5 and then perform hydrothermal crystallization treatment, followed by solid-liquid separation, washing and drying to obtain high-purity vanadium pentoxide (V2O5) powder.
[0007] Furthermore, the magnetic vanadium spinel in S1 has the following mass percentage composition: V2O3 15-55wt%, Cr2O3 0-15wt%, TiO2 5-15wt%, FeO 15-50wt%, MnO3-15wt%, SiO2 1-20wt%, P≤0.005wt%.
[0008] Furthermore, the magnetic separation condition described in S1 is 0.3-0.5T multi-physics field magnetic separation.
[0009] Furthermore, the particle size of the milling process described in S1 is 50-70 μm. The weak magnetic separation conditions are 0.3-0.5T, the ultrasonic dispersion conditions are 20-25kHz treatment for 8-12min, and the particle size range of the highly active vanadium spinel powder is 20-70μm.
[0010] Further, in S2, the mass ratio of the composite additive to the highly active vanadium spinel powder is 2-10:10; the mass ratio of Na2CO3 to MgCO3 is 10:2-10, and the mass ratio of Na2CO3 to MnCO3 is 10:2-10; the mass ratio of the highly active vanadium spinel powder to Fe2O3 is 100:1-8; the calcination temperature is 400-850℃, and the calcination time is 5 min-240 min; the pH of the aqueous solution is 2.5-7.
[0011] Furthermore, in the vanadium-containing leachate described in S2: vanadium concentration ≥ 2 g / L, Cr ≤ 0.001 mg / L, Fe ≤ 2 mg / L, P ≤ 0.1 mg / L, Si ≤ 20 mg / L, Mn 2+ ≤100mg / L.
[0012] Furthermore, the pH value of S3 is 1.8-2.8; the volume percentage of the composite extraction system is: 20-50 vol% P2O4 or P5O7, 5-15 vol% TBP, and 40-80 vol% sulfonated kerosene.
[0013] Furthermore, the conditions for the mixed extraction described in S3 include: extraction at room temperature for 10-60 min; and the sulfuric acid concentration for the sulfuric acid back-extraction is 3-6 M H₂SO₄.
[0014] Furthermore, the oxidant mentioned in S5 includes hydrogen peroxide, air, or oxygen.
[0015] Furthermore, the conditions for hydrothermal crystallization include: holding at 120-220℃ for 2-24 hours; and the drying temperature is 110-120℃.
[0016] A vanadium oxysulfate electrolyte or high-purity vanadium pentoxide prepared by the above method.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention utilizes an inert atmosphere composite additive controllable roasting system to directly and selectively prepare tetravalent vanadium in one step, eliminating the need for subsequent external reducing agents and high-valent vanadium reduction processes. This completely avoids the cumbersome process of roasting pentavalent vanadium and then additionally reducing it to prepare tetravalent vanadium, significantly shortening the vanadium electrolyte preparation process, reducing the cost of reducing agent consumables and process energy consumption, and preventing the introduction of new impurities during the reduction process, thus ensuring the purity and stability of vanadium oxysulfate (VOSO4) electrolyte from the source.
[0018] 2. This invention employs a composite additive argon atmosphere selective roasting process, relying on gradient alkaline hydrolysis and lattice selective dissociation mechanisms to achieve efficient vanadium leaching, passivation and insolubility of chromium, titanium, iron, and phosphorus impurities, resulting in high vanadium-chromium separation selectivity. It utilizes the addition of Fe2O3 to preferentially react with the manganese component in the solid phase to form a sparingly soluble manganese-iron spinel solid solution, FeMnO3 / MnFe2O4, fixing manganese in the clinker solid phase. Simultaneously, it innovatively employs a P204 / P507-TBP-sulfonated kerosene ternary synergistic extraction system, leveraging the advantages of TBP in demulsification, impurity suppression, and accelerated phase separation to further enhance the extraction selectivity of tetravalent vanadium. The leachate can be directly extracted and purified without complex impurity removal processes, significantly simplifying the process and reducing production costs. The entire process of this invention exhibits a strong coupling relationship: the directional preparation of tetravalent vanadium leachate through an inert atmosphere and composite additives is a prerequisite for the direct extraction preparation of VOSO4 electrolyte without reduction; and the high-purity tetravalent vanadium electrolyte is the basis for the direct crystallization of highly crystalline V2O5 under hydrothermal conditions without ammonium. Existing technologies disclose magnetic separation, roasting, extraction, and hydrothermal vanadium precipitation separately, but none of them disclose the complete process chain in which the upstream and downstream are interdependent; it is not a simple series connection of individual units.
[0019] 3. The Na2CO3-MgCO3 / MnCO3 composite additive valence state buffering and regulation system adopted in this invention uses a method of directly obtaining tetravalent vanadium by calcining Na2CO3-MnCO3-Fe2O3 or Na2CO3-MgCO3-Fe2O3, while simultaneously fixing manganese in the residue; it breaks through the technical bottleneck of traditional calcination that cannot control valence, precisely locking tetravalent vanadium through weak oxidation-micro reduction coupling effect, eliminating the generation of pentavalent vanadium by-products, and solving the industry pain point of traditional processes that require secondary reduction from the metallurgical mechanism. This composite regulation system breaks through the technical bottleneck of single sodium salt calcination at 800°C only producing pentavalent vanadium and requiring reduction to obtain tetravalent vanadium, and has a high technical barrier.
[0020] 4. Single-process focused preparation of high-purity vanadium for vanadium batteries. The process is highly specific and stable, and can stably produce first-grade VOSO4 vanadium battery electrolyte. The product has high purity and no impurities, making it perfectly suited for high-end applications of all-vanadium redox flow batteries, resulting in extremely high added value.
[0021] 5. The method employs a short-process core technology of hydrothermal enhancement for straight-crystal vanadium precipitation in an acidic system with pH=2.8, which overturns the technical understanding of zero precipitation at room temperature and pressure in Comparative Example 4. It breaks through the thermodynamic barrier at room pressure, enabling the originally stable and non-precipitating pentavalent vanadium solution to crystallize and precipitate efficiently, with a vanadium precipitation rate as high as 99.69%. At the same time, it achieves controllable product morphology, optimizing the loose flocculent agglomerates of the traditional process into blocky V2O5 single crystal particles with complete crystal shape and dense structure. It completely solves the defects of traditional high-purity vanadium preparation process, such as many grain defects, impurity enrichment, and poor product purity and stability. The obtained product fully meets the standards for high-purity raw materials for vanadium batteries, and the product quality far exceeds that of traditional processes.
[0022] 6. Flexible and adaptable processes and diversified product matrix: It can selectively produce first-grade VOSO4 vanadium electrolyte for energy storage batteries or high-purity vanadium pentoxide (V2O5) powder for high-end energy storage batteries according to market and production needs. The dual products have high added value and are suitable for multiple application scenarios of vanadium battery energy storage. The process adaptability and industrial competitiveness are extremely strong.
[0023] 7. The overall process is closed-loop and green and low-carbon. The tailings washing liquid is recycled and reused, and there is no waste liquid discharge. Combined with the low-energy consumption design of low-temperature roasting, low-temperature extraction and low-temperature hydrothermal throughout the process, it takes into account both resource utilization efficiency and industrial adaptability, and has outstanding industrial value. Attached Figure Description
[0024] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 This is a schematic diagram of a short-process method for preparing high-purity vanadium for vanadium batteries according to the present invention. Detailed Implementation
[0026] To better understand the technical solution of the present invention, the embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0027] Example 1
[0028] A short-process method for preparing high-purity vanadium for vanadium batteries, the method comprising the following steps: S1. Raw material pretreatment: Magnetic vanadium spinel is obtained by magnetic separation of converter vanadium slag; the magnetic vanadium spinel is then subjected to grinding, weak magnetic separation and ultrasonic dispersion to obtain highly active vanadium spinel powder. S2. Preparation and extraction of tetravalent vanadium by calcination of composite additives: The high-activity vanadium spinel powder described in S1 is mixed with composite additives and then transferred to a heating furnace for calcination in an argon atmosphere. The calcined clinker is added to an aqueous solution at 25-95℃ for leaching, and then filtered to separate vanadium-containing leachate and vanadium leaching tailings. The composite is Na2CO3-MnCO3-Fe2O3 or Na2CO3-MgCO3-Fe2O3. S3. Preparation of vanadium oxysulfate (VOSO4) electrolyte by extraction: Add acid to the vanadium-containing leachate described in S2 to adjust the pH value to acidic, and then sequentially pass it through a composite extraction system for mixed extraction, washing and purification with dilute sulfuric acid, and sulfuric acid back-extraction-graphite degreasing to obtain vanadium oxysulfate (VOSO4) electrolyte; the composite extraction system includes: a ternary compound system with P204 or P507 as the main extractant, TBP as the co-extraction agent, and sulfonated kerosene as the diluent; S4. Harmless treatment of tailings: The vanadium leaching tailings described in S2 are washed with warm water at 40-60℃ 2-4 times to obtain washing liquid, which is then used in the leaching process described in S2 for recycling. S5. One-step oxidation-hydrothermal direct precipitation of vanadium to prepare high-purity vanadium pentoxide (V2O5): Take the vanadium oxysulfate (VOSO4) electrolyte described in S3, add an oxidant to completely oxidize tetravalent vanadium to pentavalent vanadium, adjust the pH of the system to 1.2-3.5 and then perform hydrothermal crystallization treatment, followed by solid-liquid separation, washing and drying to obtain high-purity vanadium pentoxide (V2O5) powder.
[0029] Furthermore, the magnetic vanadium spinel in S1 has the following mass percentage composition: V2O3 15-55wt%, Cr2O3 0-15wt%, TiO2 5-15wt%, FeO 15-50wt%, MnO3-15wt%, SiO2 1-20wt%, P≤0.005wt%.
[0030] Furthermore, the magnetic separation condition described in S1 is 0.3-0.5T multi-physics field magnetic separation.
[0031] Furthermore, the particle size of the milling process described in S1 is 50-70 μm. The weak magnetic separation conditions are 0.3-0.5T, the ultrasonic dispersion conditions are 20-25kHz treatment for 8-12min, and the particle size range of the highly active vanadium spinel powder is 20-70μm.
[0032] Further, in S2, the mass ratio of the composite additive to the highly active vanadium spinel powder is 2-10:10; the mass ratio of Na2CO3 to MgCO3 is 10:2-10, and the mass ratio of Na2CO3 to MnCO3 is 10:2-10; the mass ratio of the highly active vanadium spinel powder to Fe2O3 is 100:1-8; the calcination temperature is 400-850℃, and the calcination time is 5 min-240 min; the pH of the aqueous solution is 2.5-7.
[0033] Furthermore, in the vanadium-containing leachate described in S2: vanadium concentration ≥ 2 g / L, Cr ≤ 0.001 mg / L, Fe ≤ 2 mg / L, P ≤ 0.1 mg / L, Si ≤ 20 mg / L, Mn 2+The vanadium content is ≤300 mg / L, and the vanadium residue in the vanadium leaching tailings is <0.1 wt%.
[0034] Furthermore, the pH value of S3 is 1.8-2.8; the volume percentage of the composite extraction system is: 20-50 vol% P2O4 or P5O7, 5-15 vol% TBP, and 40-80 vol% sulfonated kerosene; the ratio of aqueous phase to organic phase in the extract is 1:0.4-2.
[0035] Furthermore, the conditions for the mixed extraction described in S3 include: extraction at room temperature for 10-60 min; the sulfuric acid concentration of the sulfuric acid back-extraction is 3-6 M H₂SO₄, and the ratio of aqueous phase to organic phase in the sulfuric acid back-extraction solution is 1:1-7.
[0036] Furthermore, the oxidant mentioned in S5 includes hydrogen peroxide, air, or oxygen.
[0037] Furthermore, the conditions for hydrothermal crystallization include: holding at 120-220℃ for 2-24 hours; and the drying temperature is 110-120℃.
[0038] A vanadium oxysulfate electrolyte or high-purity vanadium pentoxide prepared by the above method.
[0039] Example 2
[0040] A novel method for preparing high-purity vanadium for vanadium batteries using a short process includes the following steps: S1. Raw material pretreatment: The raw material is selected from converter vanadium slag or magnetic vanadium spinel obtained by magnetic separation of converter vanadium slag; if the raw material is converter vanadium slag, it is first separated by 0.3-0.5T multi-physical field magnetic separation to obtain magnetic vanadium spinel intermediate material. If the raw material is magnetic vanadium spinel directly, no pre-magnetic separation is required; the obtained magnetic vanadium spinel is uniformly ground to 50-70μm, and then further enriched with vanadium components by 0.3-0.5T weak magnetic separation, and then dispersed by 20-25kHz ultrasonic dispersion for 8-12min to break up the magnetic agglomerates, to obtain highly active vanadium spinel powder with a size range of 20-70μm; The magnetic vanadium spinel has the following composition: V2O3 15-55wt%, Cr2O3 0-15wt%, TiO2 5-15wt%, FeO 15-50wt%, MnO 3-15wt%, SiO2 1-5wt%, P≤0.005wt%, covering the full composition range of conventional industrial converter vanadium slag and suitable for vanadium slag raw materials from different origins and under different smelting conditions.
[0041] S2. One-step directional preparation of tetravalent vanadium by calcination with composite additives: The highly active vanadium spinel powder prepared in S1 is mixed with Na2CO3-MnCO3-Fe2O3 and Na2CO3-MgCO3-Fe2O3 composites, and then transferred to a heating furnace for calcination under an argon atmosphere. The mass ratio of composite additives to vanadium slag is 2-10:10, the mass ratio of Na2CO3 to MgCO3 or MnCO3 is 10:2-10, and the mass ratio of vanadium slag to Fe2O3 is 100:1-8. The calcination temperature is 400-850℃, and the calcination time is 5min-240min. After calcination, calcined clinker is obtained. The clinker is added to a leaching solution for leaching, and the vanadium-containing leachate and inert tailings are obtained by filtration. This step achieves selective and efficient leaching of vanadium with precise control of its valence state, generating tetravalent vanadium components in one step. The vanadium leaching rate is ≥90%, the chromium leaching rate is ≤0.005%, and phosphorus is almost insoluble. The resulting leachate contains vanadium concentrations ≥2g / L, Cr≤0.001mg / L, Fe≤2mg / L, P≤0.1mg / L, Si≤20mg / L, and Mn≤300mg / L, thus achieving complete and efficient separation of vanadium from chromium, titanium, iron, and phosphorus impurities.
[0042] S3. Direct preparation of vanadium oxysulfate (VOSO4) electrolyte by extraction: Add an adjusting solution to the vanadium-containing leachate obtained in S2 to adjust the pH to 1.8-2.8. No impurity removal or reduction pretreatment is required; the solution is directly mixed with the composite extraction system. The composite extraction system uses a ternary synergistic system with P507 or P204 as the main extractant, TBP as the extraction aid, and sulfonated kerosene as the diluent. The organic phase volume ratio is: main extractant (P507 / P204) 20%–50%, TBP extraction aid 5%–15%, and sulfonated kerosene 40%–80%. This ternary system can significantly improve the selective extraction capability of tetravalent vanadium, reduce impurity co-extraction, accelerate phase separation, and avoid extraction emulsification. Extraction is performed at room temperature for 10-60 minutes, followed by phase separation. Washing is done with low-concentration sulfuric acid, followed by back-extraction with 3-6M sulfuric acid, controlling the aqueous / organic phase ratio at 1:2-5. Finally, the solution is degreased using graphite to obtain a high-purity first-grade VOSO4 vanadium electrolyte. S4. Harmless treatment of tailings: The inert tailings obtained in S2 are washed multiple times with warm water. The washing liquid is returned to the vanadium leaching process for recycling. After washing, the tailings are disposed of in compliance with regulations after solid waste harmless treatment, without secondary pollution.
[0043] S5. One-step oxidation-hydrothermal direct precipitation of vanadium to prepare high-purity vanadium pentoxide (V₂O₅): Take the high-purity tetravalent vanadium electrolyte obtained in S3, and use hydrogen peroxide, air, or oxygen as oxidants for isothermal forced oxidation to remove V₂O₅ from the system. 4+ Completely oxidized to V 5+After oxidation, the pH of the system is adjusted to 1.2, and the mixture is transferred to a hydrothermal reactor. The high-temperature and high-pressure hydrothermal environment drives the direct in-situ crystallization and growth of vanadate ions, generating V2O5 crystals in one step without the need to prepare ammonium polyvanadate precursors or perform high-temperature calcination. After the reaction, the mixture is cooled, filtered, washed with water, and dried to directly obtain high-purity nano / flaky V2O5 powder with a vanadium precipitation rate of ≥99% and a product purity of ≥99.5%.
[0044] Example 3
[0045] This embodiment provides a novel method for preparing high-purity vanadium for vanadium batteries using a short process. The specific steps are as follows: S1. Raw material pretreatment: Vanadium slag from converters was selected as raw material and magnetic vanadium spinel was obtained by 0.4T multi-physical field magnetic separation. The mass fraction of the raw material composition was: V2O3 38wt%, Cr2O3 8wt%, SiO2 2.1wt%, P 0.002wt%, FeO 32wt%, MnO 8wt%, TiO2 9.9wt%. The magnetic vanadium spinel was ground to 60μm and further enriched with vanadium components by 0.4T weak magnetic separation. Then, it was dispersed by ultrasonic dispersion at 22kHz for 10min to break up the magnetic agglomerates, and finally, highly active vanadium spinel powder with uniform particle size of 20-60μm was obtained.
[0046] S2. Vanadium extraction by calcination with composite additives: The prepared high-activity vanadium spinel powder was uniformly mixed with Na2CO3-MgCO3 composite additives. The mass ratio of composite additives to vanadium slag was 6:10, and the mass ratio of Na2CO3 to MgCO3 was 10:6. The mixture was placed in an argon atmosphere calcination furnace and calcined at a constant temperature of 750℃ for 120 min. After calcination, the clinker was added to a solution at 60℃ and pH=2.8 for leaching. Solid-liquid separation was performed by vacuum filtration to obtain high-purity vanadium-containing leachate and titanium-chromium-rich inert tailings. In this embodiment, the vanadium leaching rate can reach 93.5%, the vanadium concentration of the leachate is stable at 20.6 g / L, Cr and P were not detected, Fe content was ≤0.05 g / L, and Mn was 6.5 g / L.
[0047] Example 4
[0048] This embodiment provides a novel method for preparing high-purity vanadium for vanadium batteries using a short process. The specific steps are as follows: S1. Raw material pretreatment: Vanadium slag from converters was selected as raw material and magnetic vanadium spinel was obtained by 0.4T multi-physical field magnetic separation. The mass fraction of the raw material composition was: V2O3 38wt%, Cr2O3 8wt%, SiO2 2.1wt%, P 0.002wt%, FeO 32wt%, MnO 8wt%, TiO2 9.9wt%. The magnetic vanadium spinel was ground to 60μm and further enriched with vanadium components by 0.4T weak magnetic separation. Then, it was dispersed by ultrasonic dispersion at 22kHz for 10min to break up the magnetic agglomerates, and finally, highly active vanadium spinel powder with uniform particle size of 20-60μm was obtained.
[0049] S2. Vanadium extraction by calcination of the composite: The prepared highly active vanadium spinel powder was uniformly mixed with the Na2CO3-MgCO3-Fe2O3 composite. The mass ratio of the composite to vanadium slag was 6:10, the mass ratio of Na2CO3 to MgCO3 was 10:6, and the mass ratio of vanadium slag to Fe2O3 was 100:5. The mixture was placed in an argon atmosphere calcination furnace and calcined at a constant temperature of 750℃ for 120 min. After calcination, the clinker was added to a solution at 60℃ and pH=2.8 for leaching. Solid-liquid separation was performed by vacuum filtration to obtain high-purity vanadium-containing leachate and titanium-chromium-rich inert tailings. In this embodiment, the vanadium leaching rate reached 94.3%, the vanadium concentration of the leachate was stably 21.2 g / L, Cr and P were not detected, Fe content was ≤0.05 g / L, and Mn ≤85 mg / L. The impurity separation effect was excellent.
[0050] S3. Preparation of vanadium oxysulfate (VOSO4) electrolyte: The pH of the vanadium-containing leaching solution was adjusted to 2.3 with dilute sulfuric acid. No impurity removal or reduction pretreatment was required. The ternary composite extraction system of 40% P2O4 + 5% TBP + 55% sulfonated kerosene was directly used for extraction at room temperature for 30 min. After extraction, the solution was washed with low-concentration sulfuric acid to remove impurities. Then, 4.5M sulfuric acid was used for back-extraction, and the ratio of aqueous phase to organic phase was controlled at 1:3. Finally, the solution was degreased by graphite to obtain a clear and impurity-free first-grade VOSO4 vanadium electrolyte for energy storage.
[0051] S4. Harmless treatment of tailings: The titanium-chromium-rich inert tailings obtained from roasting are washed multiple times with 50°C warm water. All washing liquid is returned to the leaching process for recycling, achieving a closed-loop process with no waste liquid discharge. The washed tailings are solidified and stabilized before being disposed of in compliance with regulations and without secondary pollution.
[0052] S5. One-step oxidation-hydrothermal direct vanadium precipitation preparation of high-purity vanadium pentoxide (V2O5): The prepared high-purity VOSO4 vanadium electrolyte is used for constant-temperature oxidation with hydrogen peroxide to completely oxidize the tetravalent vanadium in the system to pentavalent vanadium. The pH of the system is adjusted to 2.8. Under normal temperature and pressure conditions, the acidic vanadium solution in this system is thermodynamically stable, with no hydrolysis or vanadium precipitation, and the precipitation rate is 0%. The solution is transferred to a closed hydrothermal reactor and hydrothermally enhanced crystallization is carried out at 180℃ for 12 hours. The high temperature and high pressure environment breaks the thermodynamic barrier of normal-pressure precipitation, driving the in-situ dehydration, rearrangement, and directional crystallization growth of vanadate. After the reaction, the solution is naturally cooled, filtered, washed with deionized water until neutral, and dried at a constant temperature of 120℃ to obtain high-purity blocky V2O5 crystal powder in one step. The product completely abandons the flocculent agglomeration structure of traditional processes, with complete crystal shape and dense structure, a vanadium precipitation rate of up to 99.69%, and a product purity of 99.65%.
[0053] Example 5
[0054] This embodiment provides a novel method for preparing high-purity vanadium for vanadium batteries using a short process. The specific steps are as follows: S1. Raw material pretreatment: Finished magnetic vanadium spinel is directly selected as raw material, with the following composition by mass fraction: V2O3 28wt%, Cr2O3 5wt%, SiO2 1.8wt%, P 0.0025wt%, FeO 38wt%, MnO 10wt%, TiO2 11.4wt%. The raw material is ground to 50μm, enriched with vanadium active components by 0.3T weak magnetic separation, and then dispersed by 20kHz ultrasonic dispersion for 12min to break up the powder agglomeration, so as to obtain highly active vanadium spinel powder with uniform dispersion and excellent activity.
[0055] S2. Vanadium extraction by calcination using composite additives: A Na2CO3-MnCO3-Fe2O3 composite system was selected. The composite was uniformly mixed with vanadium spinel powder at a mass ratio of 6:10, the mass ratio of Na2CO3 to MnCO3 was 10:6, and the mass ratio of vanadium slag to Fe2O3 was 100:8. The material was placed in an argon inert atmosphere calcination furnace and calcined at a constant temperature of 800℃ for 120 minutes. The calcined clinker was leached in a solution at 60℃ and pH=2.8, and the solid and liquid were separated by vacuum filtration to obtain a high-purity vanadium-containing leachate and inert tailings. In this embodiment, the vanadium leaching rate reached 98.8%, the vanadium concentration of the leachate was 19.5 g / L, the impurity content was extremely low, Cr and P were not detected, the Fe content was ≤0.05 g / L, and Mn ≤250 mg / L, meeting the requirements for direct extraction and purification.
[0056] S3. Preparation of vanadium oxysulfate (VOSO4) electrolyte: The pH of the leaching solution was adjusted to 1.9 using dilute sulfuric acid. A ternary composite extraction system of 40% P507 + 5% TBP + 55% sulfonated kerosene was selected and extracted at room temperature for 50 min. After extraction, the solution was washed and purified with low-concentration sulfuric acid, and back-extracted with 3M sulfuric acid. The ratio of aqueous phase to organic phase was controlled at 1:2. Finally, the solution was purified by graphite degreasing to obtain a qualified energy storage-grade VOSO4 vanadium electrolyte.
[0057] S4. Harmless treatment of tailings: The roasting tailings are washed multiple times with 40℃ warm water, and the washing liquid is returned to the leaching process in a closed loop for recycling, so as to achieve efficient utilization of resources; the solid tailings after washing are disposed of in compliance with regulations after harmless stabilization treatment, without secondary solid waste pollution.
[0058] S5. One-step oxidation-hydrothermal direct vanadium precipitation to prepare high-purity vanadium pentoxide (V2O5): Oxygen bubbling oxidation for 30 min completely oxidizes tetravalent vanadium in the electrolyte to pentavalent vanadium; the pH of the system is controlled at 2.8, and the solution system is stable under normal temperature and pressure conditions, with no hydrolysis precipitation and no vanadium ion precipitation; the solution is transferred to a closed hydrothermal reactor and subjected to constant temperature closed hydrothermal crystallization at 180℃ for 12 h, relying on the high temperature and high pressure coupling effect to break the barrier of normal pressure vanadium precipitation, driving the in-situ ordered crystal growth of vanadate; after the reaction, the solution is cooled and filtered, washed with deionized water, and dried at constant temperature of 110℃. The obtained V2O5 is a blocky single crystal particle with complete crystal form and dense structure, completely eliminating the flocculent agglomeration defects of traditional processes, with a stable vanadium precipitation rate of 99.08% and a product purity of 99.33%.
[0059] Example 6
[0060] This embodiment provides a novel method for preparing high-purity vanadium for vanadium batteries using a short process. The specific steps are as follows: S1. Raw material pretreatment: vanadium slag from converters is selected as raw material and purified by 0.5T multi-physical field magnetic separation to obtain magnetic vanadium spinel. The magnetic vanadium spinel is ground to 70μm and then enriched with vanadium components by 0.5T weak magnetic separation. The powder is then dispersed by 25kHz ultrasonic dispersion for 8 minutes to break up the agglomerates and prepare vanadium spinel powder with uniform particle size and high reactivity.
[0061] S2. Vanadium extraction by calcination of the composite: The pretreated vanadium spinel powder was mixed with the Na2CO3-MgCO3-Fe2O3 composite. The mass ratio of the composite to vanadium slag was 9:10, the mass ratio of Na2CO3 to MgCO3 was 10:9, and the mass ratio of vanadium slag to Fe2O3 was 100:5. The mixture was calcined at 850℃ for 120 min under an inert argon atmosphere. The calcined clinker was then leached in a solution at 60℃ and pH=2.8, followed by solid-liquid separation to obtain a high-purity vanadium-containing leachate. In this embodiment, the vanadium leaching rate reached 97.5%, the vanadium concentration in the leachate was 25.3 g / L, and Mn ≤ 90 mg / L.
[0062] S3. Preparation of vanadium oxysulfate (VOSO4) electrolyte: The pH of the leachate was adjusted to 2.8 using dilute sulfuric acid. A ternary composite extraction system of 40% P2O4 + 5% TBP + 55% sulfonated kerosene was selected and extracted at room temperature for 15 min. After extraction, the solution was washed and purified with low-concentration sulfuric acid, and then back-extracted with 6M sulfuric acid at a high efficiency. The ratio of aqueous phase to organic phase was controlled at 1:5. Finally, the solution was degreased by graphite to obtain ultra-high purity first-grade VOSO4 vanadium electrolyte.
[0063] S4. Harmless treatment of tailings: The roasting tailings are washed twice with 60℃ warm water, with the solid-liquid ratio controlled at 1:6. All washing liquid is recycled to the leaching process. After washing, the tailings are solidified by keeping them at 480℃ for 1.5h and then disposed of in compliance with regulations, forming a green closed loop process.
[0064] S5. One-step oxidation-hydrothermal direct vanadium precipitation for the preparation of high-purity vanadium pentoxide (V2O5): Low-temperature oxidation with hydrogen peroxide is used to completely convert tetravalent vanadium in the electrolyte into pentavalent vanadium; the pH of the system is controlled at 2.8, and the vanadium-containing solution is stable under normal temperature and pressure conditions, with no hydrolysis and no vanadium precipitation; the solution is transferred to a hydrothermal reactor and subjected to constant temperature hydrothermal intensification crystallization at 180℃ for 12 hours. Through high temperature and high pressure coupling, efficient and directional crystallization of vanadate is achieved, generating complete blocky V2O5 crystals in one step; the product abandons the flocculent and loose aggregated structure of traditional processes, with regular and dense crystals, complete crystal shape and no defects, and the final vanadium precipitation rate is stable at 99.69%, and the product purity is 99.63%.
[0065] Example 7
[0066] This embodiment uses low-vanadium, high-titanium, and high-iron industrial converter vanadium slag as raw material to provide a novel short-process method for preparing high-purity vanadium for vanadium batteries. The specific steps are as follows: S1. Raw material pretreatment: Low-vanadium, high-titanium, and high-iron converter vanadium slag is selected and magnetic vanadium spinel is obtained by 0.3T multi-physical field magnetic separation. The raw material composition mass fraction is: V2O3 18.5wt%, Cr2O3 3.2wt%, TiO2 14.2wt%, FeO 46.8wt%, MnO 4.5wt%, SiO2 2.5wt%, P 0.004wt%. The magnetic vanadium spinel is ground to 55μm, and the vanadium component is enriched by 0.3T weak magnetic separation. The magnetic agglomerates are dispersed by 20kHz ultrasonic dispersion for 12min to obtain uniform-sized and highly active vanadium spinel powder.
[0067] S2. Vanadium extraction by calcination with composite additives: Highly active vanadium spinel powder is uniformly mixed with Na2CO3-MgCO3-Fe2O3 composite additives. The mass ratio of composite additives to vanadium slag is 8:10, the mass ratio of Na2CO3 to MgCO3 is 10:8, and the mass ratio of vanadium slag to Fe2O3 is 100:5. The mixture is placed in an argon atmosphere calcination furnace and calcined at 800℃ for 120 min. The calcined clinker is leached with a solution at 60℃ and pH=2.8, and separated by filtration to obtain a high-purity vanadium-containing leachate and titanium-chromium-rich inert tailings. In this embodiment, the vanadium leaching rate is 95.2%, the vanadium concentration in the leachate is 22.4 g / L, Cr and P are not detected, Fe content is ≤0.06 g / L, Mn ≤80 mg / L, and most of the titanium and chromium impurities are solidified in the tailings, achieving efficient separation of vanadium from impurities.
[0068] S3. Preparation of vanadium oxysulfate (VOSO4) electrolyte: The pH of the leaching solution was adjusted to 2.1 using dilute sulfuric acid. A ternary composite extraction system of 40% P2O4 + 5% TBP + 55% sulfonated kerosene was used for extraction at room temperature for 40 min. After washing with low-concentration dilute sulfuric acid to remove impurities, back-extraction was performed using 4.0M sulfuric acid, controlling the aqueous phase / organic phase ratio at 1:4. Finally, the solution was degreased using graphite to obtain a clear, transparent, and organic-residue-free first-grade VOSO4 vanadium electrolyte (V... 4+ 89g / L, Al ≤0.1mg / L, Na ≤10mg / L, Fe ≤1mg / L, Si ≤0.1mg / L, Cr ≤0.1mg / L, Ca ≤0.2mg / L).
[0069] S4. Harmless treatment of tailings: The high-titanium iron inert tailings are washed three times with 55℃ warm water. All washing liquid is returned to the leaching process for recycling, realizing a closed-loop process. After washing, the tailings are solidified and stabilized and then disposed of in compliance with regulations and without secondary solid waste or waste liquid pollution.
[0070] S5. One-step oxidation-hydrothermal direct vanadium precipitation for the preparation of high-purity vanadium pentoxide (V2O5): Air bubbling oxidation for 40 min completely oxidizes tetravalent vanadium in the electrolyte to pentavalent vanadium; the pH of the system is controlled at 2.8, and the solution system is stable under normal temperature and pressure, with no hydrolysis and no vanadium precipitation; the solution is transferred to a closed hydrothermal reactor and hydrothermally crystallized at 180℃ for 12 h, relying on the high temperature and high pressure environment to break the thermodynamic precipitation barrier under normal pressure, driving the in-situ dehydration, rearrangement, and directional crystallization growth of vanadate; after the reaction, it is naturally cooled, filtered, thoroughly washed with deionized water, and dried at a constant temperature of 115℃, directly obtaining blocky V2O5 single crystal particles with complete crystal form and dense structure, completely avoiding the defects of traditional flocculent agglomeration, with a stable vanadium precipitation rate of 99.3% and a product purity of 99.60%.
[0071] Example 8
[0072] This embodiment uses conventional medium-grade industrial converter vanadium slag from steel mills as raw material to provide a novel short-process method for preparing high-purity vanadium for vanadium batteries. The specific steps are as follows: S1. Raw material pretreatment: vanadium slag from a conventional converter was selected and purified by 0.45T multi-physical field magnetic separation to obtain magnetic vanadium spinel. The raw material composition by mass fraction was: V2O3 32.6wt%, Cr2O3 10.5wt%, TiO2 8.6wt%, FeO3 3.2wt%, MnO 9.8wt%, SiO2 3.2wt%, P 0.003wt%. The powder was ground to 65μm and further enriched with vanadium by 0.45T weak magnetic separation. The powder was then dispersed by ultrasonication at 23kHz for 10min to break up the agglomerates and prepare highly active vanadium spinel powder.
[0073] S2. Vanadium extraction by calcination of the composite: A Na2CO3-MnCO3-Fe2O3 composite system was adopted, with the mass ratio of the composite to vanadium slag being 9:10, the mass ratio of Na2CO3 to MnCO3 being 10:9, and the mass ratio of vanadium slag to Fe2O3 being 100:8. Under an inert argon atmosphere, the calcined material was calcined at 800℃ for 120 min. The calcined material was then leached in a solution at 60℃ and pH=2.8, followed by solid-liquid separation to obtain a high-purity vanadium-containing leachate. In this embodiment, the vanadium leaching rate was 95.7%, the vanadium concentration of the leachate was 22.8 g / L, and the Mn concentration was ≤300 mg / L, which can be directly extracted and purified.
[0074] S3. Preparation of vanadium oxysulfate (VOSO4) electrolyte: The pH of the leachate was adjusted to 2.5 with dilute sulfuric acid. A ternary composite extraction system of 40% P507 + 5% TBP + 55% sulfonated kerosene was selected and extracted at room temperature for 25 min. After washing and purification with low-concentration sulfuric acid, back-extraction was performed with 3.5M sulfuric acid. The ratio of aqueous phase to organic phase was controlled at 1:3.5. After oil removal and purification, a high-quality energy storage-grade VOSO4 vanadium electrolyte was obtained.
[0075] S4. Harmless treatment of tailings: The roasting tailings are washed four times with 45℃ warm water. The washing liquid is recycled in a closed loop for the leaching process, maximizing resource utilization. The washed tailings are disposed of in compliance with regulations after being treated to achieve harmlessness and stability, resulting in green and environmentally friendly treatment without secondary pollution.
[0076] S5. One-step oxidation-hydrothermal direct vanadium precipitation preparation of high-purity vanadium pentoxide (V2O5): Hydrogen peroxide is used for constant temperature oxidation for 20 min to completely convert tetravalent vanadium in the electrolyte into pentavalent vanadium; the pH of the system is adjusted to 2.8, and the solution is stable without vanadium precipitation under normal temperature and pressure; crystallization is enhanced by closed hydrothermal heat treatment at 180℃ for 12 h, which forces the in-situ ordered crystallization growth of vanadate, and generates dense blocky V2O5 crystals with uniform and regular grains and no agglomeration defects in one step, with a vanadium precipitation rate of 99.69% and a product purity of 99.64%.
[0077] Example 9
[0078] This embodiment uses high-vanadium, low-impurity, high-quality converter vanadium slag as raw material to provide a novel short-process method for preparing high-purity vanadium for vanadium batteries. The specific steps are as follows: S1. Raw material pretreatment: High-vanadium, low-impurity high-quality converter vanadium slag is selected and purified by 0.5T multi-physical field magnetic separation to obtain magnetic vanadium spinel. The raw material composition mass fraction is: V2O3 52.3wt%, Cr2O3 2.1wt%, TiO2 6.3wt%, FeO2 2.5wt%, MnO 12.2wt%, SiO2 1.2wt%, P 0.0015wt%. The raw material is ground to 70μm, and the vanadium component is enriched by 0.5T weak magnetic separation. The powder is dispersed by 25kHz ultrasonic dispersion for 8min to break up the agglomerates and obtain highly active ultrafine vanadium spinel powder.
[0079] S2. Vanadium extraction by calcination with composite additives: The pretreated powder is mixed with Na2CO3-MgCO3-Fe2O3 composite, with a mass ratio of composite to vanadium slag of 6:10, a mass ratio of Na2CO3 to MgCO3 of 10:6, and a mass ratio of vanadium slag to Fe2O3 of 100:3. The mixture is calcined at 750℃ for 120 min under an argon inert atmosphere to rapidly activate the vanadium spinel lattice and selectively dissociate the vanadium components. In this embodiment, the vanadium leaching rate is as high as 90.4%, the vanadium concentration of the leaching solution is 19.1 g / L, and impurities such as iron, chromium, and phosphorus are almost undetectable. The purity of the leaching solution is excellent, with Mn≤150 mg / L.
[0080] S3. Preparation of vanadium oxysulfate (VOSO4) electrolyte: The pH of the leaching solution was adjusted to 2.0 with dilute sulfuric acid. A ternary composite extraction system of 40% P2O4 + 5% TBP + 55% sulfonated kerosene was selected and extracted at room temperature for 20 min. After washing and high-efficiency back-extraction with 6M sulfuric acid, the ratio of aqueous phase to organic phase was controlled at 1:5. Finally, the solution was degreased by graphite to obtain ultra-high purity first-grade vanadium electrolyte.
[0081] S4. Harmless treatment of tailings: The roasting tailings are washed twice with 60℃ warm water, and the washing liquid is recycled to the leaching process. The tailings have extremely low impurity content and can be disposed of in compliance with regulations after simple solidification treatment. The process is simple, green and low-carbon.
[0082] S5. One-step oxidation-hydrothermal direct vanadium precipitation for the preparation of high-purity vanadium pentoxide (V2O5): Oxygen bubbling oxidation is used to completely convert tetravalent vanadium in the electrolyte into pentavalent vanadium; the pH of the system is controlled at 2.8, and the solution is thermodynamically stable at room temperature and pressure with no precipitation; after 12 hours of hydrothermal enhanced crystallization at 180℃, the nucleation limitation at normal pressure is broken, driving the directional and orderly growth of vanadate ions to directly generate highly crystalline, dense blocky V2O5 crystals; the product has complete crystal shape, no defects, no agglomeration, a stable vanadium precipitation rate of 99.50%, and a product purity of up to 99.68%.
[0083] Example 10
[0084] A novel method for preparing high-purity vanadium for vanadium batteries using a short process, the specific steps of which are as follows: S1. Raw material pretreatment: vanadium slag from converters is selected as raw material and purified by 0.5T multi-physical field magnetic separation to obtain magnetic vanadium spinel. The magnetic vanadium spinel is ground to 70μm and then enriched with vanadium components by 0.5T weak magnetic separation. The powder is then dispersed by 25kHz ultrasonic dispersion for 8 minutes to break up the agglomerates and prepare vanadium spinel powder with uniform particle size and high reactivity.
[0085] S2. Vanadium extraction by calcination with composite additives: Pretreated vanadium spinel powder is mixed with a Na2CO3-MgCO3-Fe2O3 composite. The mass ratio of the composite to vanadium slag is 9:10, the mass ratio of Na2CO3 to MgCO3 is 10:9, and the mass ratio of vanadium slag to Fe2O3 is 100:5. Under an inert argon atmosphere, the mixture is calcined at 850℃ for 20 minutes. The calcined clinker is then leached in a solution at 60℃ and pH=2.8, followed by solid-liquid separation to obtain a high-purity vanadium-containing leachate. In this embodiment, the vanadium leaching rate can reach 97.5%, the vanadium concentration in the leachate is 25.3 g / L, and Mn ≤ 200 mg / L.
[0086] S3. Preparation of vanadium oxysulfate (VOSO4) electrolyte: The pH of the leachate was adjusted to 2.8 using dilute sulfuric acid. A ternary composite extraction system of 40% P2O4 + 5% TBP + 55% sulfonated kerosene was selected and extracted at room temperature for 15 min. After extraction, the solution was washed and purified with low-concentration sulfuric acid, and then back-extracted with 6M sulfuric acid at a high efficiency. The ratio of aqueous phase to organic phase was controlled at 1:5. Finally, the solution was degreased by graphite to obtain ultra-high purity first-grade VOSO4 vanadium electrolyte.
[0087] S4. Harmless treatment of tailings: The roasting tailings are washed twice with 60℃ warm water, with the solid-liquid ratio controlled at 1:6. All washing liquid is recycled to the leaching process. After washing, the tailings are solidified by keeping them at 480℃ for 1.5h and then disposed of in compliance with regulations, forming a green closed loop process.
[0088] S5. One-step oxidation-hydrothermal direct vanadium precipitation for the preparation of high-purity vanadium pentoxide (V2O5): Low-temperature oxidation with hydrogen peroxide is used to completely convert tetravalent vanadium in the electrolyte into pentavalent vanadium; the pH of the system is controlled at 3.5, and the vanadium-containing solution is stable under normal temperature and pressure conditions, with no hydrolysis and no vanadium precipitation; the solution is transferred to a hydrothermal reactor and subjected to constant temperature hydrothermal intensification crystallization at 180℃ for 12 hours. Through high temperature and high pressure coupling, efficient and directional crystallization of vanadate is achieved, generating complete blocky V2O5 crystals in one step; the product abandons the flocculent and loose aggregated structure of traditional processes, with regular and dense crystals, complete crystal shape and no defects, and the final vanadium precipitation rate is stable at 99.08%, and the product purity is 99.33%.
[0089] Comparative Example 1 A single Na₂CO₃ argon roasting technology. This process uses converter vanadium slag as raw material, with uniform operating parameters: carbonate / vanadium slag mass ratio = 40:100, roasting temperature 800℃, holding time 2h, and roasting in an inert argon atmosphere throughout. Under these standard parameters, the alkaline oxidation potential of sodium carbonate during high-temperature roasting is extremely strong. Even in an inert atmosphere, it cannot inhibit the deep oxidation of vanadium, resulting in V in vanadium spinel. 3+ Completely oxidized to V 5+ The final leaching product is only a pentavalent vanadium solution, which cannot generate tetravalent vanadium. A secondary reduction treatment with a reducing agent is required to prepare vanadium electrolyte. The process is complicated, energy-intensive, and prone to introducing impurities, making it impossible to achieve the core technical effect of "one-step directional generation of tetravalent vanadium without reduction" of this invention.
[0090] Comparative Example 2 A single MnCO3 argon roasting technology was used. This process employed converter vanadium slag, the same material as in Comparative Example 1, with the following uniform operating parameters: carbonate / vanadium slag mass ratio = 40:100, roasting temperature 900℃, holding time 2h, and roasting in an inert argon atmosphere. The single manganese carbonate high-temperature roasting system lacks strong alkali activating components, resulting in extremely weak ability to dissociate and disrupt the dense lattice of vanadium spinel. It cannot effectively break the vanadium-oxidation chemical bonds. Even with an increased roasting temperature of 900℃ and a longer roasting time of 2h, vanadium components remained difficult to dissolve, ultimately achieving a measured vanadium leaching rate of less than 1%. This is essentially not industrially viable for vanadium extraction, only achieving trace vanadium oxidation, and completely failing to meet the demands of efficient industrial vanadium extraction.
[0091] Comparative Example 3 A single MgCO3 argon roasting technology. This process uses vanadium slag from a homogeneous converter as raw material, and is matched with uniform comparison conditions: carbonate / vanadium slag mass ratio = 40:100, roasting temperature 900℃, holding time 2h, and argon inert atmosphere roasting. The single magnesium carbonate high-temperature roasting system has insufficient lattice activation and alkaline dissociation potential energy, which cannot fully deconstruct the stable structure of vanadium spinel. Even with high-temperature long-time roasting to enhance the reaction, the effective vanadium leaching efficiency is extremely low, with a measured vanadium leaching rate of only about 50%. Nearly half of the vanadium resources remain in the tailings and cannot be utilized. The vanadium resource utilization rate is low, the industrial economics are extremely poor, and efficient resource-based vanadium extraction cannot be achieved.
[0092] Comparative Example 4 This invention relates to a conventional pentavalent vanadium pH-controlled precipitation technique. The technique focuses on vanadium precipitation from pentavalent vanadium leaching solutions obtained through conventional roasting. Under normal temperature and pressure conditions, when the pH of the purified pentavalent vanadium solution is adjusted to 2.8, the spontaneous precipitation rate of vanadium is zero, and the vanadium solution remains stable without hydrolysis or crystallization. In acidic, atmospheric-pressure systems, pentavalent vanadium cannot spontaneously nucleate and crystallize. Therefore, traditional vanadium precipitation processes rely on the addition of ammonium salts to prepare ammonium polyvanadate precursors, followed by high-temperature calcination to obtain V₂O₅. This process is lengthy, energy-intensive, prone to ammonium salt residue leading to excessive impurities in the product, and produces products with flocculent agglomerates and numerous crystal defects. Currently, there is no existing technology for direct ammonium-free crystallization and vanadium precipitation under pH 2.8 acidic conditions. The method of this invention achieves effective vanadium precipitation under pH 2.8 acidic conditions, significantly improving preparation efficiency, saving costs, and effectively reducing the burden of subsequent wastewater treatment.
[0093] The core innovation of this invention lies in the use of a Na2CO3-MgCO3 / MnCO3 composite carbonate synergistic argon inert calcination system. This breaks the traditional technical constraint that the oxidation and calcination of sodium carbonate alone inevitably produces pentavalent vanadium. It achieves the directional and controllable conversion of trivalent vanadium to tetravalent vanadium in vanadium spinel, eliminating the need for subsequent reduction processes from a metallurgical perspective, while simultaneously achieving precise phase separation of vanadium, chromium, and titanium. Some of the mechanisms involved are as follows: 1. Inert atmosphere inhibits deep oxidation and locks in the target vanadium valence state: Traditional air / oxygen roasting systems have high oxygen partial pressure, resulting in low vanadium valence state in vanadium spinel. 3+ It is easily oxidized to V. 5+ The product is mainly pentavalent vanadium sodium vanadate (NaVO3), requiring the addition of a reducing agent to prepare tetravalent vanadium oxysulfate (VOSO4) electrolyte. This invention utilizes argon inert protection throughout the process, and the extremely low oxygen partial pressure of the system only supports V... 3+ →V 4+ First-order moderate oxidation completely blocks V 4+ To V 5+ The deep oxidation pathway enables the control of the valence state of tetravalent vanadium from the perspective of atmospheric environment.
[0094] 2. Magnesium / Manganese carbonate weak oxidation-micro reduction coupling for precise pricing of tetravalent vanadium: High-temperature roasting of Na₂CO₃ alone is too alkaline and reacts violently, easily causing excessive oxidation of vanadium and disrupting the crystal lattice. The combined MgCO₃ and MnCO₃ possess mild thermal decomposition characteristics and valence state buffering effects: on the one hand, the decomposition of carbonates produces trace amounts of active oxygen, which can be released in a controlled manner, only reducing the stable V₂ in the vanadium spinel lattice. 3+ Activated to soluble V 4+ On the other hand, the MgO and MnO generated by decomposition are weakly reducing alkaline oxides, which can act as a valence buffer layer to immediately suppress the formation of local over-oxygen micro-regions and prevent the formation of pentavalent vanadium by-products. In the end, vanadium in the roasted clinker exists in the form of soluble tetravalent vanadate solid solution.
[0095] 3. Gradient alkaline hydrolysis with composite additives selectively deconstructs the vanadium spinel lattice: Vanadium spinel is a stable composite metal oxide lattice, which is difficult to selectively dissociate using conventional reagents. Na₂CO₃ provides a strong alkaline substrate, preferentially breaking the vanadium-oxygen bond, achieving efficient dissociation of the vanadium component; MgCO₃ / MnCO₃ regulates the alkalinity of the system and the calcination reaction rate, avoiding simultaneous erosion of the chromium and titanium lattices under strong alkaline conditions and high temperatures. This gradient alkaline hydrolysis mechanism achieves directional dissociation of the vanadium lattice while preserving the complete chromium and titanium lattice, which is the core mechanism for achieving high vanadium leaching and extremely low chromium and titanium dissolution. Chromium and titanium are stably retained in the residue, laying the foundation for subsequent stepwise high-purity extraction.
[0096] 4. Impurity passivation mechanism to ensure ultra-high purity of leachate: Mg in the system 2+ Mn 2+ It can form stable, insoluble phosphate and silicate precipitates with impurity ions such as phosphorus and silicon, achieving in-situ sealing of impurities; at the same time, the low-temperature controllable roasting system avoids the large-scale activation and dissolution of the iron phase, ultimately achieving a high-purity leaching effect with almost insoluble phosphorus and trace amounts of iron and chromium. No pre-purification is required, and it can be directly extracted to prepare first-grade vanadium electrolyte, or it can be directly used for subsequent oxidation-hydrothermal precipitation of vanadium to prepare high-purity vanadium pentoxide (V2O5).
[0097] In traditional roasting processes, manganese exists in the form of CaMnO3 or Mn2SiO4. Under leaching conditions of pH=2.8, it enters the leachate, resulting in a manganese content as high as 8-10 g / L, making manganese-vanadium separation difficult. To avoid manganese leaching during the leaching stage, Fe2O3 is innovatively added during the roasting stage to transform the manganese phase in the vanadium slag into the acid-insoluble form of (Fe,Mn)3O4 or FeMnO3, thus avoiding leaching at pH=2.8. This invention does not achieve completely zero manganese leaching, but rather reduces the manganese content in the leachate from 8000-10000 mg / L in traditional processes to below 300 mg / L. The remaining small amount of manganese impurities can be further separated and removed in the extraction process, ultimately yielding a vanadium electrolyte that meets the standards for vanadium batteries.
[0098] 5. Core Innovative Mechanism of Vanadium Battery-Grade High-Purity Vanadium Pentoxide (V₂O₅) Preparation by Directed Oxidation-Hydrothermal Direct Crystallization of Tetravalent Vanadium: Traditional high-purity vanadium preparation processes require the preparation of ammonium polyvanadate followed by high-temperature calcination to obtain V₂O₅. This process is lengthy, prone to grain agglomeration and impurity accumulation during high-temperature calcination, and consumes a lot of energy. The purity of the product is insufficient to meet the high-end requirements of vanadium batteries. This invention, relying on a high-purity tetravalent vanadium electrolyte system, employs a unique homogeneous oxidation-hydrothermal direct crystallization coupling mechanism, representing a disruptive short-process high-purity vanadium preparation technology. Firstly, V₂O₅ is prepared through gentle homogeneous oxidation... 4+ Completely converted to V 5+Vanadate ions are produced without any impurities co-precipitating in the system. Secondly, utilizing the synergistic effect of pressure and temperature in a closed hydrothermal system, the vanadate ions undergo in-situ dehydration, rearrangement, and crystallization, directly generating high-purity crystalline vanadium pentoxide (V₂O₅) in one step, skipping the precursor preparation and calcination decomposition stages. This mechanism completely solves the problems of high energy consumption, numerous powder defects, and large purity fluctuations associated with traditional calcination processes. The resulting product has complete crystallization, uniform particle size, and extremely high purity, fully meeting the high-purity raw material standards for vanadium batteries.
[0099] The core creative breakthrough of this invention compared to existing technologies: 1. Synergistic effects of compound additives overcome the limitations of single-system parameters and solve industry technical bottlenecks: This invention abandons the shortcomings of fixed parameters in comparative examples 1-3 for single carbonates. Based on vanadium slag raw materials from the same source under electron microscopy, it innovatively adopts a Na2CO3-MgCO3 / MnCO3 compound system, breaking through the technical bottlenecks of single sodium salt roasting at 800℃ producing only pentavalent vanadium and single magnesium / manganese carbonate having extremely low leaching rates after long-term roasting at 900℃. Through compound additive ratio control and temperature adaptation optimization, this invention achieves low-temperature, short-time, high-efficiency vanadium extraction and directional generation of tetravalent vanadium without the need for ultra-high temperatures of 900℃ or long-term roasting of 2 hours. It achieves a high leaching rate of over 90% and precise valence state control, resulting in a synergistic effect that is completely impossible to achieve under fixed parameter conditions, and its effectiveness is highly evident.
[0100] 2. Precise valence state locking under inert atmosphere, overturning traditional roasting mechanisms: Unlike the inherent defect of single sodium salt roasting in Comparative Example 1, which inevitably produces pentavalent vanadium, this invention precisely blocks V under an argon inert atmosphere through a weak oxidation-micro reduction coupling mechanism of composite additives. 4+ To V 5+ Deep oxidation directly generates high-purity tetravalent vanadium leachate in one step, completely eliminating the reduction process and breaking through the problem of valence state loss control in traditional roasting processes from a metallurgical mechanism perspective.
[0101] 3. Breaking through conventional vanadium precipitation technology, achieving acidic ammonium-free direct crystallization, and meeting the needs of high-purity vanadium preparation for vanadium batteries: In response to the conventional technical understanding of "no precipitation of pentavalent vanadium at pH=2.8" disclosed in Comparative Example 4, this invention utilizes the special physicochemical environment of high temperature and high pressure in a closed hydrothermal system and in-situ dehydration and rearrangement to break through the thermodynamic limitations of atmospheric pressure vanadium precipitation. Under conditions of no ammonium, no precursor, and no high-temperature calcination, pentavalent vanadium is directly crystallized in an acidic system to generate battery-grade high-purity vanadium pentoxide (V2O5) crystals with a vanadium precipitation rate of ≥99%. This subverts the traditional high-purity vanadium preparation process and is a disruptive short-process innovation.
[0102] 4. Precise impurity passivation, product purity adapted to high-end vanadium battery applications: The composite additive system of this invention can passivate phosphorus, iron, and chromium impurities in situ, resulting in ultra-high purity leachate. Combined with the advantages of hydrothermal straight crystal without impurity entrainment, it can simultaneously prepare first-grade vanadium electrolyte for vanadium batteries and battery-grade high-purity vanadium pentoxide (V2O5) with a purity of over 99.5%. The product quality and process adaptability far exceed all single comparative technologies, demonstrating significant industrialization advantages.
[0103] The embodiments of the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A short-process method for preparing high-purity vanadium for vanadium batteries, characterized in that, The method includes the following steps: S1. Raw material pretreatment: Magnetic vanadium spinel is obtained by magnetic separation of converter vanadium slag; the magnetic vanadium spinel is then subjected to grinding, weak magnetic separation and ultrasonic dispersion to obtain highly active vanadium spinel powder. S2. Preparation and extraction of tetravalent vanadium by calcination of composite additives: The highly active vanadium spinel powder described in S1 is mixed with the composite and then transferred to a heating furnace for calcination under an argon atmosphere. The calcined clinker is added to an aqueous solution at 25-95℃ for leaching, and then filtered to separate the vanadium-containing leachate and vanadium leaching tailings. The composite is Na2CO3-MnCO3-Fe2O3 or Na2CO3-MgCO3-Fe2O3. S3. Preparation of vanadium oxysulfate electrolyte by extraction: Add acid to the vanadium-containing leachate described in S2 to adjust the pH value to acidic, and then sequentially pass it through a composite extraction system for mixed extraction, washing and purification with dilute sulfuric acid, and sulfuric acid back-extraction-graphite degreasing to obtain vanadium oxysulfate electrolyte; the composite extraction system includes: a ternary compound system with P204 or P507 as the main extractant, TBP as the co-extraction agent, and sulfonated kerosene as the diluent; S4. Harmless treatment of tailings: The vanadium leaching tailings described in S2 are washed with deionized water 2-4 times at 40-60℃ to obtain washing liquid, which is then used in the leaching process described in S2 for recycling. S5. One-step oxidation-hydrothermal direct precipitation of vanadium to prepare high-purity vanadium pentoxide: Take the vanadium oxysulfate electrolyte described in S3, add an oxidant to completely oxidize tetravalent vanadium to pentavalent vanadium, adjust the pH of the system to 1.2-3.5 and then perform hydrothermal crystallization treatment, followed by solid-liquid separation, washing and drying to obtain high-purity vanadium pentoxide powder.
2. The method according to claim 1, characterized in that, The magnetic vanadium spinel in S1 has the following mass percentage composition: V2O3 15-55wt%, Cr2O3 0-15wt%, TiO 25-15wt%, FeO 15-50wt%, MnO 3-15wt%, SiO 21-20wt%, P≤0.005wt%.
3. The method according to claim 1, characterized in that, The magnetic separation condition described in S1 is 0.3-0.5T multi-physics field magnetic separation.
4. The method according to claim 1, characterized in that, The particle size of the milling process described in S1 is 50-70 μm. The weak magnetic separation conditions are 0.3-0.5T, the ultrasonic dispersion conditions are 20-25kHz treatment for 8-12min, and the particle size range of the highly active vanadium spinel powder is 20-70μm.
5. The method according to claim 1, characterized in that, The mass ratio of the composite additive to the highly active vanadium spinel powder in S2 is 2-10:10; the mass ratio of Na2CO3 to MgCO3 is 10:2-10, and the mass ratio of Na2CO3 to MnCO3 is 10:2-10; the mass ratio of the highly active vanadium spinel powder to Fe2O3 is 100:1-8; the calcination temperature is 400-850℃, and the calcination time is 5 min-240 min; the pH of the aqueous solution is 2.5-7.
6. The method according to claim 1, characterized in that, The vanadium-containing leachate in S2 contains: vanadium concentration ≥ 2 g / L, Cr ≤ 0.001 mg / L, Fe ≤ 2 mg / L, P ≤ 0.1 mg / L, Si ≤ 20 mg / L, Mn 2+ ≤300mg / L.
7. The method according to claim 1, characterized in that, The pH value of S3 is 1.8-2.8; the volume percentage of the composite extraction system is: 20-50 vol% P204 or P507, 5-15 vol% TBP, and 40-80 vol% sulfonated kerosene.
8. The method according to claim 7, characterized in that, The conditions for the mixed extraction described in S3 include: extraction at room temperature for 10-60 min; and the sulfuric acid concentration for the sulfuric acid back-extraction is 3-6 M H₂SO₄.
9. The method according to claim 1, characterized in that, The oxidant in S5 includes hydrogen peroxide, air, or oxygen, and the conditions for hydrothermal crystallization include: holding at 120-220°C for 2-24 hours; and the drying temperature is 110-120°C.
10. A vanadium oxysulfate electrolyte or high-purity vanadium pentoxide prepared by any one of the methods described in claims 1-9.